2018
DOI: 10.1177/0954406218755184
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on machinability of different electrode materials for SEAM of the nickel-based superalloy GH4169

Abstract: The short electric arc machining technology is a technical category of electrical machining in the special machining industry. It further improves machining efficiency (1.92 × 105 mm3/min) in comparison to other electrical machining. In short electric arc machining, the electrode materials directly affect the surface quality of the workpiece, electrode loss, and dimensional accuracy. Therefore, the selection of the electrode material is particularly important. Using the nickel-based superalloy GH4169 machining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Arc machining has the advantages of high removal efficiency and continuous and stable discharge, which provides an efficient and feasible means for realizing the efficient machining of difficultto-cut materials. 11,12 In 2001, General Electric (GE) designed BlueArcä technology for the efficient cutting of superalloy materials widely used in aircraft engines and power turbines. Research institutions and scholars in China have put forward different arc processing methods in recent years, and the large amount of related research work conducted has greatly promoted the application of arc processing in the field of special processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arc machining has the advantages of high removal efficiency and continuous and stable discharge, which provides an efficient and feasible means for realizing the efficient machining of difficultto-cut materials. 11,12 In 2001, General Electric (GE) designed BlueArcä technology for the efficient cutting of superalloy materials widely used in aircraft engines and power turbines. Research institutions and scholars in China have put forward different arc processing methods in recent years, and the large amount of related research work conducted has greatly promoted the application of arc processing in the field of special processing.…”
Section: Introductionmentioning
confidence: 99%
“…Arc machining has the advantages of high removal efficiency and continuous and stable discharge, which provides an efficient and feasible means for realizing the efficient machining of difficult-to-cut materials. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2020) studied the effect of electrode polarity on DC short arc milling of titanium alloys and found that electrode negative machining can yield a higher machining e ciency [14]. Li et al (2018) studied the in uence of different electrode materials on pulse short arc milling and found that graphite provides a lower electrode loss rate, whereas red copper provides better surface quality [15]. Chen et al…”
Section: Introductionmentioning
confidence: 99%
“…It is an original innovative technology in China. 11,12 It uses the tangential slip between the tool and the workpiece electrode under the hydrodynamic force of the gas-liquid mixed working fluid to achieve arc drawing and arc breaking in SEAM. Ti-6Al-4V is a titanium alloy with a þ b dual-phase structure.…”
Section: Introductionmentioning
confidence: 99%